Psychosocial risks factors and burnout in police officers: a network analysis - Ruiz-Ruano García, Ana María; Blaya Sánchez, Miguel Ángel; López Morales, José Luis; Peinado Portero, Ana Isabel; Giner Alegría, César Augusto; López Puga, Jorge; Moya-Faz, Francisco J. (Anales de Psicología / Annals of Psychology, 2023)
Work stress has been identified as a critical factor affecting mental health in police officers. Psychosocial factors increase the impact of work stress on police officers and, in the long run, contribute to the onset of burnout symptoms. In this research a sample of 323 was studied to study the relationship between psychosocial risk factors and the probability of suffering burnout symptoms. The participant’s answers to the MBI-GS and F-PSICO (version 4.0) were analysed by using network analysis. The results show that psychosocial risk factors are strongly associated in network models when higher level of cynicism and emotional exhaustion are observed. Additionally, higher levels of burnout in police officers were observed when lower autonomy, higher psychological demands, role ambiguities and a lower perceived social support were present. Results are discussed considering its theoretical and applied relevance to design healthier work environments and efficient psychological interventions.